Measuring the maturity of Indian small and medium enterprises for unofficial readiness for capability maturity model integration‐based software process improvement. Issue 9 (7th April 2020) - Singh, Ashima; Gill, Sukhpal Singh
Abstract: Establishing the maturity levels of ‐ Small and Medium Enterprises (SMEs) without Capability Maturity Model Integration (CMMI) certification has always been regarded as an extremely challenging task. Software process improvement (SPI) has targeted to monitor and improve software processes, thereby improving the software business. Although there is scientific interest in SPI, little attention has been specifically given to the exploration of maturity levels for non‐CMMI SMEs. The goal is to explore the effect of time on process maturity and maturity levels achieved informally or unofficially by SMEs that are not otherwise CMMI certified. To find out the maturity levels achieved informally, a CMMI‐DEV v1.3 based survey questionnaire is administered to Indian software SMEs. Time of establishment of SMEs and follow‐up of CMMI‐based processes and practices unofficially are used as two important parameters to decide upon process maturity and achievement of specific CMMI level informally. This paper has been successful in ascertaining the effect of time of establishment of SMEs and follow‐up of CMMI‐based processes on process maturity using proposed RuleML that advocates adoption of more than 70% of CMMI‐DEV v1.3 process area‐specific practices for an SME to be unofficially ready for CMMI‐based SPI initiatives. The findings manifest multidimensional aspects of unofficial readiness of SMEs for CMMI‐based SPI that can be used by relevant authorities to select SMEs for funding for SPI initiatives. Finally, the proposed work has been validated statistically using t ‐test for CMMI Level II and Level III. Abstract : Multidimensional aspects have been identified for unofficial readiness of small and medium enterprises (SMEs) for Capability Maturity Model Integration (CMMI)‐based software process involvement (SPI) that can be used by relevant authorities to select SMEs for funding for the SPI initiatives. The time of establishment of SMEs, follow‐up of CMMI‐based process areas‐specific practices (PAs‐SPs), critical success factors for SPI, informal maturity ratings based on CMMI‐Dev v1.3, and Rule ML are the key highlights of the presented approach for assessing the maturity of non‐CMMI SMEs.